An Approach to the Intellectual Contents of the Three Lamias (Arabs and Turkish Non-Arabs) in the Light of Comparative Literature - محمود حیدری; مريم اشراق پور (آداب الكوفة, 2018)
The opposition between literary monuments is a phenomenon that has afflicted the world of literature since historical times, and perhaps between different nations, and Arabs are fond of writing oppositions, matching, dividing poems, dividing them, and simulating them. Poets throughout the ages have sought to oppose the effects of their well-known counterparts, admiring them or emphasizing their superiority over them. Among these oppositions, which received great attention, were the opposition of the Lamiyyat, as many poets opposed it, including the opposition of al-Tughrafi in his poem Lamiyat al-Ajam, the poem of the Lamiyat of the Arabs by al-Shanfriuth, the opposition of Nir al-Tabrizi, the poem of Lamiyat al-Ajam in his poem marked Lamiyat al-Turk.